Case Report: Detection of Treponema phagedenis in cerebrospinal fluid of a neurosyphilis patient by metagenomic next-generation sequencing - Yuan, Chenyan; Xu, Wei; Zhao, Chenggui; Gao, Wei; Wu, Guoqiu (Frontiers in Cellular and Infection Microbiology, 2023)
Treponema phagedenis, a human commensal spirochete, has been reported world-wide as a key factor in the pathogenesis of bovine digital dermatitis. Here we report a case of T. phagedenis sequence detection in the cerebrospinal fluid (CSF) of a patient. The patient was diagnosed with neurosyphilis, and T. phagedenis was detected as the only microorganism in his CSF by metagenomic sequencing. The patient went through a round of penicillin therapy previously (2.4 million units of Benzathine Penicillin intramuscularly once a week for three weeks) that did not resolve the symptoms; after the diagnosis of neurosyphilis he was treated with Penicillin G Sodium 4.0 million units q4h intravenous for 14 days then his symptoms resolved. To the best of our knowledge, T. phagedenis has never been reported to be detected in a human’s CSF before. This was also the first time it was detected by metagenomic next-generation sequencing. We propose that more etiological tests should be performed including culture and sequencing for more patients with syphilis, which will contribute to a deeper understanding of the pathogenicity of the spirochete.